2017
DOI: 10.26502/ami.9365006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasites in Vegetables Sold in Some Local Markets in Port-Harcourt, Rivers-State, Nigeria

Abstract: A total of 492 vegetable leaves samples made up of cabbage (27), bitter leaves (50), garden egg leaves (44), green leaves (66), green onion (47), lettuce (51), pumpkin leaves (111), parsley (26) and water leaves (70), bought randomly from various local markets in Port-Harcourt was analyzed for the presence of some parasite stages. About 145(29.5%) out 492 samples examined were contaminated with various parasite stages. Green leaves had the highest level of contamination (40.9%), followed by bitter leaves (38.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 17 publications
4
11
1
Order By: Relevance
“…In 2017, two separate studies reported the screening of parasites in vegetables sold in selected markets in Port Harcourt. In these studies, Mbata et al, [21] reported a contamination rate of 85% compared to 29.5% by Tchounga et al, [14]. The variation of reports from these researchers in Port Harcourt markets could be due to the hygiene practices of the farmers and sellers.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In 2017, two separate studies reported the screening of parasites in vegetables sold in selected markets in Port Harcourt. In these studies, Mbata et al, [21] reported a contamination rate of 85% compared to 29.5% by Tchounga et al, [14]. The variation of reports from these researchers in Port Harcourt markets could be due to the hygiene practices of the farmers and sellers.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies carried out in some markets in Port Harcourt metropolis have shown that several fruits and vegetables were contaminated with helminths eggs (such as Ancyclostoma spp, Ascaris lumbricoides, Strongyloides stercoralis, Fasciola spp); as well as protozoan trophozoites, cyst, oocyst (such as Giardia lamblia, Cryptosporidium spp, Entamoeba coli, Entamoeba histolytica, Toxoplasma gondii and Balantidium coli), [21,14].…”
Section: Ascarismentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen publications out of the 68 publications reported contamination of fruits and vegetables with the subject parasites. The prevalence of Cryptosporidium on fresh produce (fruits and vegetables) ranged from 0.8% ( Tchounga et al, 2017 ) to over 80% ( Saaed and Ongerth, 2019 ). Most publications that reported the parasites in vegetables/fruits were from West Africa (8/12), this review did not capture any article from the Central and Southern African region ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“… Wastewater Algeria 100% Hamaidi-Chergui et al, 2019 Vegetables/fruits Ethiopia 15–16% Tefera et al, 2014 ; Bekele et al, 2017 Vegetables Libya 16–26 Abougrain et al, 2010 Hymenolepis nana Wastewater Algeria 100% Hamaidi-Chergui et al, 2019 Wastewater & sludge Tunisia 14% Khouja et al, 2010 Sewage Tunisia 18% Ben Ayed et al, 2009 Vegetables Egypt 3% El Said Said, 2012 Vegetables/fruits Ethiopia 8–16% Tefera et al, 2014 ; Bekele et al, 2017 ; Chilo et al, 2018 Hymenolepis diminuta Wastewater Algeria 100% Hamaidi-Chergui et al, 2019 Vegetables/fruits Ethiopia 1–8% Tefera et al, 2014 ; Bekele et al, 2017 Fasciola spp. Vegetables Ghana 0.2–7% Duedu et al, 2014 ; Kudah et al, 2018 Nigeria 8–78% Amaechi et al, 2016 ; Tchounga et al, 2017 ; Chijioke et al, 2018 …”
Section: Resultsmentioning
confidence: 99%